TECHNOLOGICAL INDICATORS OF COMMON VARIETIES OF MEDIUM-SIZED POTATOES - Васьковская, Светлана; Мулярчук, Оксана; Слободяник, Галина; Денисюк, Валентин; Войцеховский, Владимир; Орловский, Николай (SWorldJournal, 2021)
The results of analysis industrial evaluation of potato tubers of different varieties of middle-late ripeness are presented. It is set that sorts Promin, Aladin, Sifra, Olviya and Pikasso most valuable among investigated.